Haji Dalam Budaya Masyarakat Bugis Barru: Suatu Pergeseran Makna - Nasruddin Nasruddin (Jayapangus Press, 2020)
This research aims to reveal the change of the symbolic meaning of pilgrimage. Type of this research uses a qualitative approach. The research subjects were people who have carry out the pilgrimage. Data were collected through observation, interview and documentation technique. The data were analyzed through qualitative descriptive using phenomenology approach. The result of this research revealed that the forms of the change of pilgrimage symbolic meaning are shown through the ceremony of mappatoppo and construction clothes of the pilgrim. Factors encouraging those changes were social status and prestige asa well as expected appreciation.